The Role of Information Literacy in Shaping Students' Character Values in Primay Education Schools - Novi Oktaria., Eni Amaliah, (Jurnal El-Pustaka, 2024)
This research examines the character of students who must be developed to become elementary school teachers who have noble character and are in line with the demands of the times. In this case, lectures on ethics and the teaching profession will be used as a forum for character education for PGSD students, and efforts will be made to improve the character of PGSD students. A professional teacher is a teacher who does not only rely on teaching materials, but also upholds moral quality values and a professional code of ethics. In this study, we investigated (1) the characteristics of novice elementary school teachers; (2) Planning for developing character values in ethics and vocational education courses. (3) Steps for professional and educational ethics courses to contribute to the education of character values (4) Integrity of professional ethics and educational ethics courses in developing student character (5) Evaluating the process of implementing ethics and professional education courses.